Evaluation of Exposure to Negative Acts and Levels of Burnout among White Collar Employees in a Social Security Center in İstanbul - (:unkn) unknown (My University, 2020)
Workplace bullying is continuous and repetitive behavior that can lead to many negative physical and emotional consequences for employees. It is thought to be a problem that can cause more destructive consequences on employees than all other stress factors related to work. In this study, it is aimed to evaluate the levels of exposure to negative acts of and its effect on burnout level of employees in a Social Security Center. The population of this cross-sectional study consists of 350 people who work in a Social Security Center in Istanbul. The data of the study was obtained from a survey filled by the participants in January-February 2019. The survey includesquestions about sociodemographic characteristics, the Negative Acts Questionnaire-Revised (NAQ-R) which is used to assess damaging behaviors at work, and the Burnout Measure-Short Version (BMS) to measure burnout caused by workplace and professional life.A total of 308 people (participation rate: 88%) were included in the study. Most of the participants were male (63.6%) and faculty/college graduates (68.2%). The increase in the level of education significantly increased the NAQ-R and the BMS scores (p <0.001 and p=0.004 respectively). The BMS scores of women was significantly higher than that of men (p <0.001). In our study, a positive, moderate (Rho: 0.544) and significant (p <0.01) correlation was found between the participants' NAQ-R scores and BMS scores.